Narrative review on recent outbreaks of monkeypox: a global public health emergency - Abburu, Alekhya; Venkateswaran, Sabarish; Depa, Vineeth Reddy (International Journal of Research in Medical Sciences, 2025)
Several cases of monkeypox have been reported since July 2022 and was hence declared a global public health emergency (GPHE). Recent reports from WHO indicate a rise in mpox cases over 2 years, even when vaccination is considered a protective measure. In this review, we discussed the recent spread of cases worldwide from 1st January 2024 to 1st October 2024, providing updated evidence on clinical features of different strains, epidemiology, diagnosis, treatment, and preventive measures. Ever since the 2022 outbreak, monkeypox virus has been undergoing novel mutations, leading to different strains at an alarming rate. According to the Ministry of Health, India has reported a total of 30 cases to date with the most recent case reported in September 2024. Recent outbreaks from Clade Ib were reported among young males with a median age of 34 years and sexual contact being a common mode of transport. Mpox commences with prodromal flu-like symptoms and a maculopapular rash with centrifugal distribution followed by fever. Diagnosis is confirmed by PCR testing of the lesions. Prompt vaccination after exposure might reduce the risk of disease progression. However, antiviral treatments and symptomatic care should be considered for severe patient populations. This review gives an insight into the current mpox scenario by educating people on emerging global endemics and their preventive strategies. Unlike other neglected diseases, we now have treatment and prevention options for mpox, but access to treatment is limited in most parts of the world. Identification and spread of new cases can be tracked more efficiently with the help of improved surveillance methods.